(untitled) (LEARNing Landscapes, 2017)
This paper reports on the results of an exploratory evaluation of a sexuality education program that was introduced in technical and vocational institutions in Guyana. The rationale for the program is outlined, along with the methodology employed in the evaluation of the program, including the analysis of data from document reviews, telephone and face-to-face interviews, and surveys of facilitators and students’ perceptions of the program. The findings of the evaluation are presented and the author offers some considerations to be taken into account when developing and implementing new programs.